Neutrophil to Lymphocyte Ratio as a Predictor of Poor Prognosis in Metastatic Pancreatic Cancer Patients Treated with Nab-Paclitaxel plus Gemcitabine: A Propensity Score Analysis. (10th June 2018) - Ventriglia, J.; Petrillo, A.; Huerta Alváro, M.; Laterza, M. M.; Savastano, B.; Gambardella, V.; Tirino, G.; Pompella, L.; Diana, A.; Iovino, F.; Troiani, T.; Martinelli, E.; et al.
Abstract : Background . High neutrophil to lymphocyte ratio (NLR) has shown to be a predictor of poor outcomes in various malignancies, including pancreatic cancer. Methods . We assessed 70 consecutive pts with histologically confirmed mPC who received chemotherapy with nab-paclitaxel/gemcitabine at two different European oncologic centers between January 2012 and November 2015. Variables assessed for prognostic correlations included age ≥ 66, sex, Karnofsky PS score, primary tumor site, baseline CA19.9 level ≥ 59xULN, 12-week decrease of the CA19.9 level ≥ 50% from baseline, basal bilirubin level, baseline NLR, biliary stent implantation, and liver metastasis. Survival analyses were generated according to the Kaplan-Meier method. Univariate and multivariate analyses were performed by a Cox proportional hazard model. Results . According to NLR values, the patients were divided into two groups: high and low. Low group patients showed a better median PFS (7 months versus 5 months) and median OS (13 months versus 7 months) in respect to high group patients. At multivariate analysis, Karnofsky PS < 80% (HR = 0.4; CI 0.2–1.2), liver metastases (HR = 0.4; CI 0.18–0.82), and NLR ≥ 5 (HR = 2.7; 95% CI 1.4–5.2) were predictors of poorer OS. Based on the presence of one or more independent prognostic factors, three risk categories were identified: good-risk, intermediate-risk and poor-risk. The median OS was 22, 10, and 7 months, respectively. Conclusions . Baseline NLR is an independent predictor of survival of patients with mPC receiving palliative chemotherapy and could be useful to develop a simple clinical score to identify a subgroup of patients with a low chance to benefit from chemotherapy.